Indication of connectivity of the disperse material; MATEC Web of Conferences; Vol. 23 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment - Razva A. S. Aleksandr Sergeevich (2015, 2015)
Title screen